Post-Disaster Psychological Trauma Recovery and Support: A Study on Mental Health Services in Disaster-Prone Areas of the Philippines - Hu, Yue (International Journal of Public Health and Medical Research, 2025)
This study examines the challenges and prospects of mental health services in disaster-prone areas of the Philippines. Natural disasters frequently result in significant psychological impacts on survivors, including anxiety, depression, and post-traumatic stress disorder (PTSD). However, existing mental health services remain inadequate due to cultural stigma, a shortage of trained professionals, and limited resources. To address these gaps, the study proposes strengthening community-based mental health capacities, implementing public education campaigns to combat stigma, and incorporating mental health initiatives into disaster recovery frameworks. These measures are essential for improving disaster recovery outcomes and fostering long-term community resilience.